On the analyticity of solutions of $\overrightarrow{2b}$-parabolic systems - Ivasyshen, S. D.; Kondur, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
It is proved that if the coefficients of a $\overrightarrow{2b}$ -parabolic system admit analytic extension to a complex region in the space variables, then the fundamental matrix of solutions of the Cauchy problem and regular solutions of the system also possess the same property.